Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/2319510x211013598
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Adoption of Payment Banks in India Using an Extended TAM

Abstract: The purpose of this study is to investigate the factors that shape behavioural intentions of customers towards the adoption of payment banks in India. The conceptual framework of study is based upon integration of technology acceptance model with initial trust, facilitating conditions and social influence. Further, the study tests the moderating role of age, income and self-efficacy on the relationships between dependent variable and associated predicted variable. A total of 507 responses were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…The former refers to the public feeling of "the use of e-government platform to meet their expectations to participate in environmental governance", the more public expectation is met, the higher performance is expected. The latter refers to the public think of "using E-government platform to participate in environmental governance", the less effort, the simpler the operation, the higher the EE [24][25][26]. Previous studies have found that the higher the public expectation of performance, the greater the motivation to participate in environmental governance.…”
Section: Impact Of Public Expectation On E-government Adoption Practicesmentioning
confidence: 99%
“…The former refers to the public feeling of "the use of e-government platform to meet their expectations to participate in environmental governance", the more public expectation is met, the higher performance is expected. The latter refers to the public think of "using E-government platform to participate in environmental governance", the less effort, the simpler the operation, the higher the EE [24][25][26]. Previous studies have found that the higher the public expectation of performance, the greater the motivation to participate in environmental governance.…”
Section: Impact Of Public Expectation On E-government Adoption Practicesmentioning
confidence: 99%
“…PU is "The degree to which an individual believes that using a specific system would improve his or her job performance" (Davis, 1993, p. 476). An individual will accept a technology if he or she gets certain advantages from it and believes it will assist them in achieving their objectives (Kaur et al, 2020). Lin (2010) explained PU in the e-recruitment context as the ability of job-seekers to get career information (pay, perks, rewards and other basic components) while also, increasing their chances of getting the job.…”
Section: Literature Review and Hypotheses Formation 21 Technology Ado...mentioning
confidence: 99%
“…Innovative technologies that are simple to handle and learn are more inclined to be adopted (Chauhan et al, 2019). PEOU is one of the most pertinent elements that might influence the adoption of innovation by shaping the intentions (Kaur et al, 2020). The ease with which e-recruitment may be used to complete job applications may increase the probability of adopting it (Parikh et al, 2021).…”
Section: Literature Review and Hypotheses Formation 21 Technology Ado...mentioning
confidence: 99%
“…Here, the authors were able to explain 67.5% of the behavioral intention of adoption of PBs through their proposed model. Another study by Kaur et al ( 2020 ) has explored the behavioral intention to adopt PBs through extended technology acceptance model (TAM). TAM relies upon an individual’s perception of the usefulness of a particular technology and perceived ease of use to study the usage of a particular technology.…”
Section: Research Background and Review Of The Literaturementioning
confidence: 99%
“…Given the novelty of these differentiated banks, a grounded theory approach has been adopted to identify factors and understand the underlying dynamics. Gupta et al ( 2019 ) and Kaur et al ( 2020 ) have explored customer adoption intention with regard to PB. While the former has used the Unified Theory of Acceptance and Use of Technology (UTAUT) along with perceived credibility as a construct, the latter has used the Technology Acceptance Model (TAM).…”
Section: Introductionmentioning
confidence: 99%